ENGLISH ROMANTICISM AND ITS DEVELOPMENT - Xudoyberdiyeva Marjona Sunatillo qizi,; Khamitov Eldorbek, (Лучшие интеллектуальные исследования, 2024)
English Romanticism was a literary and artistic movement that emerged in the late 18th century and flourished throughout the 19th century. It was characterized by a focus on imagination, emotion, nature, individualism, and the supernatural. This abstract provides an overview of the development of English Romanticism, highlighting its key features and major contributors.